Evaluating Kindergarten Teachers’ Readiness for Technology-Integrated Pedagogy: An Analysis Based on the Tpack Framework - Budiarti, Erna; Shintarahayu, Balqis (FKIP Universitas Lampung, 2024)
Objective: This study evaluates kindergarten (TK) teachers' readiness to implement technology-integrated pedagogy using the TPACK (Technological Pedagogical Content Knowledge) framework. The TPACK framework combines three key dimensions: content knowledge (CK), pedagogical knowledge (PK), and technological knowledge (TK). These dimensions are essential for teachers to design and implement practical learning experiences that leverage technology. Methodology: This study uses a descriptive quantitative approach involving 50 respondents, including 40 teachers and 10 principals from kindergarten/PAUD schools in three regencies/cities in West Java: Bekasi City, Bogor Regency, and Depok City. Data were collected through a questionnaire based on TPACK aspects, namely technological knowledge (TK), pedagogical knowledge (PK), content knowledge (CK), and the integration of all three dimensions (TPACK). The data were analyzed using statistical techniques to assess teachers' readiness for integrating technology into the learning process. Findings: The findings reveal that many teachers demonstrate strong readiness in content and pedagogical knowledge. However, there is a notable gap in their mastery of technology and its application in teaching. Age, teaching experience, and access to technology training significantly influence teachers' readiness to implement the TPACK framework. Conclusion: The study concludes that while teachers possess an adequate understanding of pedagogy and content, there is a pressing need to enhance their technological skills through ongoing training and support. The implications of this study emphasize the importance of developing training programs to improve technology-related competencies for kindergarten/PAUD teachers. Such initiatives are crucial to fostering innovative teaching practices that align with the demands of modern education. Keywords: teacher readiness, pedagogy integrated technology, TPACK, education early childhood.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024149